2014
DOI: 10.2174/1389450114666140106100909
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Targeting of Cancers with Loss of PTEN Function

Abstract: Phosphatase and tensin homologue deleted on chromosome 10 (PTEN) is one of the most frequently disrupted tumor suppressors in cancer. The lipid phosphatase activity of PTEN antagonizes the phosphatidylinositol 3-kinase (PI3K)/AKT/mTOR pathway to repress tumor cell growth and survival. In the nucleus, PTEN promotes chromosome stability and DNA repair. Consequently, loss of PTEN function increases genomic instability. PTEN deficiency is caused by inherited germline mutations, somatic mutations, epigenetic and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
159
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(170 citation statements)
references
References 181 publications
2
159
1
Order By: Relevance
“…There have been limited effective solutions to solve the resistance problem in cancer treatment over the years 19, 21. Previous researches have demonstrated that PTEN is related with the drug resistance in various cancers 22. Our study gave evidence to the mechanistic connection of miR‐130b upregulation in cisplatin resistance in lung cancer.…”
Section: Discussionsupporting
confidence: 70%
“…There have been limited effective solutions to solve the resistance problem in cancer treatment over the years 19, 21. Previous researches have demonstrated that PTEN is related with the drug resistance in various cancers 22. Our study gave evidence to the mechanistic connection of miR‐130b upregulation in cisplatin resistance in lung cancer.…”
Section: Discussionsupporting
confidence: 70%
“…The mechanistic link between the unique genomic features of SccRCC and response to checkpoint antibodies is being actively investigated. For PTEN -deficient tumors, several drugs are currently under clinical development in this setting including PI3K inhibitors, AKT inhibitors and PARP inhibitors (48). Circulating biomarkers for SccRCC have not yet been formally developed, but a recent study by Pal et al detected a high rate of TP53 mutations (64%) in the circulating tumor DNA of patients with clear-cell RCC treated with later lines of vascular endothelial growth factor inhibitors versus first-line treatment (31%) (49).…”
Section: Discussionmentioning
confidence: 99%
“…PTEN can be controlled by posttranslational regulation including phosphorylation, acetylation, methylation, oxidation, and so on (42, 43). Because PTEN may be regulated by ubiquitin-mediated proteasomal degradation, a common mechanism to control protein levels, insecurity of PTEN correlated with some of its mutations has been shown to comprise protein interactions (44). Casein kinase 2 mediated phosphorylation stabilizes PTEN protein in an inactive state by inhibiting its proteasomal degradation (45, 46).…”
Section: Characteristics Of Pten and Cancermentioning
confidence: 99%